2015
DOI: 10.3947/ic.2015.47.4.239
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Clinical Characteristics of Acute Serum Creatinine Elevation more than 1.5 mg/dL among the Patients Treated with Tenofovir/Emtricitabine-containing HAART Regimens

Abstract: BackgroundThe combination of tenofovir disoproxil fumarate (TDF) and emtricitabine (FTC) has been the first choice nucleoside reverse transcriptase inhibitor (NRTI) according to many reliable antiretroviral treatment (ART) guidelines because of its high efficacy. However, TDF-related renal toxicity reported in Western countries is a challenging issue regarding clinical use. We conducted this study to evaluate the incidence and characteristics of an acute increase in serum creatinine (Cr) level > 1.5 mg/dL amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Despite the possibility of some differences in the incidence or prevalence of TDF-associated nephrotoxicity according to the measuring methods of eGFR and definition of TDF-associated nephrotoxicity, the results were broadly in line with those of other studies [6,9,15,16]. A retrospective study conducted in Korea showed that the incidence of acute Scr elevation > 1.5 mg/dL regardless of baseline Scr level among patients treated with TDF-containing regimens was 2.8 per 100 PYs [17].…”
Section: Discussionsupporting
confidence: 86%
“…Despite the possibility of some differences in the incidence or prevalence of TDF-associated nephrotoxicity according to the measuring methods of eGFR and definition of TDF-associated nephrotoxicity, the results were broadly in line with those of other studies [6,9,15,16]. A retrospective study conducted in Korea showed that the incidence of acute Scr elevation > 1.5 mg/dL regardless of baseline Scr level among patients treated with TDF-containing regimens was 2.8 per 100 PYs [17].…”
Section: Discussionsupporting
confidence: 86%
“…For eGFR and serum creatinine, TDF-associated dysfunction was defined as a 25% drop in the eGFR or a 1.5-fold increase in serum creatinine while others did not define any cutoff values for either when comparing TDF versus TAF for renal toxicity but found the TAF group had a lower reduction in eGFR. 39,40…”
Section: Discussionmentioning
confidence: 99%
“…In two of these three patients, eGRF increased after dose adjustment. Jin et al [19] reviewed a total of 136 patients taking TDF/FTC and observed a sharp increase (>1.5 mg/dL) in serum creatinine in 4.9% of the patients, all of whom were in the PI group. In our study, two of the three patients who developed nephrotoxicity were receiving a PI-based regimen.…”
Section: Discussionmentioning
confidence: 99%